The Influence of Academic Achievement, IT Proficiency, and Organizational Experience on Vocational Students’ Work Readiness: A Structural Equation Modeling Approach - Susanto, Risko Agus; Adri, Muhammad; Dewi, Ika Parma (Jurnal Vokasi Teknik Informatika, 2025)
In the era of rapid technological advancement and dynamic labor market demands, equipping vocational students with the right competencies for employability is more crucial than ever. This study explores how academic achievement, information technology proficiency, and organizational experience shape the work readiness of students in vocational education settings. Using a robust Structural Equation Modeling (SEM) approach via SmartPLS, data were collected from students at SMK Negeri 1 Linggo Sari Baganti. The results show that all three variables significantly and positively affect students' readiness for the workforce. More notably, organizational experience emerges as a key mediating factor, amplifying the influence of both academic performance and IT proficiency. This finding highlights a critical yet often overlooked aspect of employability preparation in vocational education. By integrating academic rigor, digital literacy, and active organizational participation, schools can foster a more holistic readiness among students for real-world challenges. This study contributes a fresh empirical model and offers strategic insights for policymakers and educators to design future-ready vocational curricula.